Students perceptions of Covid-19-related change to the assessment model in the postgraduate diploma (Accounting Science) - Wessels, R.; van Heerden, M.; Hassan, M. (South African Journal of Higher Education, 2025)
With the advent of the coronavirus disease in 2019 (Covid-19), several higher education institutions worldwide amended their modes of teaching and learning and the administering of assessments. This research was aimed at determining students’ perception of the changes in the assessment model from a sit-down assessment to an online assignment due to Covid-19, with specific reference to the Postgraduate Diploma (Accounting Science). It also aimed to gain insight into the self-reflection procedures that students employed with the different assessments. The study employed a quantitative approach using a survey and quantitative content analysis of the answers to the open-ended questions. Data was collected by sending out a questionnaire to three different population groups, covering both the 2020 and the 2021 class groups. The findings from the questionnaires revealed that both assessment types held advantages, as traditional assessments prepare students for future assessments, whereas assignments prove most advantageous in fostering critical thinking skills and relieving time pressure. The assignment developed certain competencies and skills not otherwise developed, and a combination of both assessments is preferable going forward.